Investigation on aromaticity index and double-bond equivalent of aromatic compounds and ionic liquids for fuel desulphurization - Abdullah, S.B. (2013)
Aromaticity index (AI) and double-bond equivalent (DBE) were studied to seek a simpler approach in identifying suitable ionic liquids for the desulphurization process. Manifestation of interaction mechanism by COSMO-RS and Raman spectroscopy is discussed. The findings demonstrate that AI and DBE calculations can be used to analyze and arrogate potential combination of cation and anion for fuel desulphurization purposes. Â© 2013 Syamsul B. Abdullah et al.